Innovation histories: A method from learning from experience - Douthwaite, B; Ashby, J (2005)
Preparing an ‘innovation history’ is a method for recording and reflec ting on an innovation process. People who have been involved in the in novation jointly construct a detailed written account (sometimes refer red to as a ‘learning history’) based on their recollections and on av ailable documents. The process of preparing this history stimulates di scussion, reflection and learning amongst stakeholders. Subsequent pla nning can build on the lessons learned, formulate a shared vision and act as a catalyst for change. Based on the initial detailed account of the innovation process, more concise informational products can be pr epared that summarize the innovation process for wider dissemination o f findings. These may include public awareness materials, policy brief s or articles in professional journals.